Kinin B1 Receptor Mediates Renal Injury and Remodeling in Hypertension - Basuli, Debargha; Parekh, Rohan Umesh; White, Acacia; Thayyil, Abdullah; Sriramula, Srinivas (Frontiers in Medicine, 2022)
Despite many readily available therapies, hypertensive kidney disease remains the second most prevalent cause of end-stage renal disease after diabetes, and continues to burden patient populations and escalate morbidity and mortality rates. Kinin B1 receptor (B1R) activation has been shown to have a role in the development of hypertension, one of the major etiologies for chronic kidney disease. However, the role of B1R in hypertension induced renal injury and remodeling remains unexplored. Using a DOCA-salt-induced hypertensive mouse model, we investigated whether B1R deficiency reduces hypertensive renal injury and fibrosis. To further recognize the translational role of B1R, we examined the expression of B1R and its correlation with collagen deposition in renal biopsies from control and hypertensive kidney disease patients. Our data indicates that renal B1R expression was upregulated in the kidneys of DOCA-salt hypertensive mice. Genetic ablation of B1R protected the mice from DOCA-salt induced renal injury and fibrosis by preventing inflammation and oxidative stress in the kidney. Cultured human proximal tubular epithelial cells expressed B1R and stimulation of B1R with an agonist resulted in increased oxidative stress. In human kidney biopsy samples, we found that the B1R immunoreactivity was not only significantly increased in hypertensive patients compared to normotensive patients, but also there is a positive correlation between B1R expression and renal fibrosis levels. Taken together, our results identify a critical role of B1R in the development of inflammation and fibrosis of the kidney in hypertension.